(untitled) (Perner’s Contacts, 2011)
This article solves the problem of general model structure of land-use and transport interaction. The modelling itself consists of partial models, which are in mutually interaction and create systematical sequence. The growth model provides estimations of indicators related to inhabitants and firms in dependence on the type of their economical activities, the land use model reflects required relations of transition of individual subjects and assignment of new settlements within their commercial activities, and finally traditional transport 4-step model with main choices of destination and transport mode and route assignment.